Using the benefits of primary health care (PHC) through women cured for breast cancer - Irzmanska-Hudziak, Anna; Gajur, Joanna; Weber, Dorota; Szadowska-Szlachetka, Zdzisława; Piasecka, Katarzyna; Stanisławek, Andrzej (Journal of Education, Health and Sport, 2018)
Admission. The treatment of patients with breast cancer over the years has changed significantly. In view of the above, these patients are more and more often long-term patients, not only oncological but also PHC. Aim: To present opinions of women being treated for breast cancer on the use of PHC services. Material and methods: The study was conducted on a group of 95 patients of oncological counseling. The research tool was the original questionnaire, GSES - Scale of Generalized Own Efficiency. The results from the obtained data were subjected to statistical analysis. Results: Older patients treated more often with PHC are treated for additional disease, apart from cancer, with a low level of their own effectiveness, with basic or vocational education. However, the services of PHC nurses are more often used by people with higher education. Patients of the oncological counseling center assess lowly the healthcare providers for oncology education. Conclusions: A small share of PHC employees in education of patients treated for breast cancer causes that oncologic outpatient clinic patients for PHC apply mainly for: obtaining a prescription, ruling or performing diagnostic tests.